2019
DOI: 10.3390/ijerph16173101
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Intermittent Hypoxia on Pulmonary Vascular and Systemic Diseases

Abstract: Obstructive sleep apnea (OSA) causes many systemic disorders via mechanisms related to sympathetic nerve activation, systemic inflammation, and oxidative stress. OSA typically shows repeated sleep apnea followed by hyperventilation, which results in intermittent hypoxia (IH). IH is associated with an increase in sympathetic activity, which is a well-known pathophysiological mechanism in hypertension and insulin resistance. In this review, we show the basic and clinical significance of IH from the viewpoint of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
33
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 73 publications
4
33
0
1
Order By: Relevance
“…There is increased recognition that OSA, characterized by intermittent hypoxia (IH), is deemed as a risk factor for the development of many cardiovascular diseases such as hypertension [ 4 ], myocardial ischemia [ 6 ], heart failure [ 7 ], atherosclerosis [ 17 ], and coronary artery disease [ 18 ]. The IH leads to a number of potential adverse consequences, including activation of inflammation [ 19 ], insulin resistance [ 20 ], oxidative stress [ 21 ], sympathetic activation [ 22 ], and endothelial dysfunction [ 23 ]. Thus, it contributes to OSA-associated cardiovascular pathologies.…”
Section: Discussionmentioning
confidence: 99%
“…There is increased recognition that OSA, characterized by intermittent hypoxia (IH), is deemed as a risk factor for the development of many cardiovascular diseases such as hypertension [ 4 ], myocardial ischemia [ 6 ], heart failure [ 7 ], atherosclerosis [ 17 ], and coronary artery disease [ 18 ]. The IH leads to a number of potential adverse consequences, including activation of inflammation [ 19 ], insulin resistance [ 20 ], oxidative stress [ 21 ], sympathetic activation [ 22 ], and endothelial dysfunction [ 23 ]. Thus, it contributes to OSA-associated cardiovascular pathologies.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of these changes during longer shifts or where additional tape is used to seal the mask further and in those workers with pre-existing cardio-respiratory disease has not been de ned. Several studies have suggested mechanistic links between chronic intermittent hypoxemia and increased production of reactive oxygen species, endothelial dysfunction, systemic in ammation, and pulmonary hypertension 13,14 , which may lead to longer-term consequences in susceptible individuals.…”
Section: Discussionmentioning
confidence: 99%
“…У пациентов ХСН с сопутствующим гемодинамиче-ски значимым поражением коронарных артерий это может также спровоцировать острую ишемию миокарда. Наряду со снижением сократительной функции ИГ напрямую или косвенно приводит к повышению давления в легочной артерии [46]. Нарушение газового состава крови и следующий за этим эпизод пробуждения (ЭЭГ-активация) вызывают увеличение тонуса симпатического отдела вегетативной нервной системы, которое сопровождается резким повышением системного артериального давления [47] и может привести к некрозу кардиомиоцитов и формированию аритмического очага [48].…”
Section: влияние центрального апноэ снаunclassified